Penerapan GTMetrix Dan K6 Dalam Pengujian Performa Dan Tingkat Stress Pada Website POS (Point Of Sale) (Studi Kasus Website waroeng99 ) - Pujo Hari Saputro (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
The development of technology which continues to increase day by day has an impact in various fields, especially in the field of sales. It has been proven that there have been many developments in sales services or services carried out online (E-commerce). in this case, of course, requires an application to process data and transactions, one of which is